Thermal and Ash Characterization of Indonesian Bamboo and Its Potential for Solid Fuel and Waste Valorization - Purbasari, Aprilina; Samadhi, Tjokorde Walmiki; Bindar, Yazid (International Journal of Renewable Energy Development, 2016)
Bamboo has been widely used in Indonesia for construction, handicrafts, furniture and other uses. However, the use of bamboo as a biomass for renewable energy source has not been extensively explored. This paper describes the thermal and ash characterization of three bamboo species found in Indonesia, i.e. Gigantochloa apus, Gigantochloa levis and Gigantochloa atroviolacea. Characterization of bamboo properties as a solid fuel includes proximate and ultimate analyses, calorific value measurement and thermogravimetric analysis. Ash characterization includes oxide composition analysis and phase analysis by X-Ray diffraction. The selected bamboo species have calorific value comparable with wood with low nitrogen and sulphur contents, indicating that they can be used as renewable energy sources. Bamboo ash contains high silicon so that bamboo ash has potential to be used further as building materials or engineering purposes. Ash composition analysis also indicates high alkali that can cause ash sintering and slag formation in combustion process. This implies that the combustion of bamboo requires the use of additives to reduce the risk of ash sintering and slag formation.Â Article History: Received May 15, 2016; Received in revised form July 2nd, 2016; Accepted July 14th, 2016; Available online How to Cite This Article: Purbasari, A., Samadhi, T.W. & Bindar, Y. (2016) Thermal and Ash Characterization of Indonesian Bamboo and its Potential for Solid Fuel and Waste Valorization. Int. Journal of Renewable Energy Development, 5(2), 95-100.http://dx.doi.org/10.14710/ijred.5.2.96-100Â